The impact of the South China Sea dispute on ASEAN Countries' Foreign Policy Toward China : A case study of the Philippines, 2013-2022 - Yao, Tingyu (2025)
The South China Sea (SCS) is vital for global trade, natural resources, and geopolitical stability. As China expanded its presence, regional disputes intensified, drawing in major powers. ASEAN, though not a direct claimant, plays a key role in promoting dialogue. Among ASEAN states, the Philippines stands out for its sharp policy shifts—from legal confrontation under Aquino (2013–2016) to economic engagement under Duterte (2016–2022). This thesis asks: Why did the Philippines, under similar pressures, pursue opposing China policies within a decade? Using the Foreign Policy Analysis (FPA) framework and a qualitative case study method, the research traces how leadership styles, domestic institutions, public opinion, and international dynamics shaped policy choices. It focuses on the period 2013–2022 draws on government documents, scholarly works, and media sources to support its findings.